Domestic Market for Jepara Wooden Furniture - K Kasmaliasari; Dodik Ridho Nurrochmat; B Bahruni; Efi Yuliati Yovi (Institut Pertanian Bogor (IPB University), 2009)
Jepara regency is the center for wooden furniture industries in Indonesia, and the products are generally marketed through a number of channels. Observed from the artisan to the last consumers, there were 5 common patterns of marketing channels in Jepara regency. The structure of the furniture market in Jepara is segmented based on product, quality, and price, therefore this condition has resulted in the monopolistic competition market structure at artisan level and showroom (furniture shops). Artisans of furniture in Jepara usually get the most orders in July, September, and December. The increase in furniture production was influenced by the religious celebrations of Idul Fitri and Christmas. The survey of furniture shops revealed that most raw materials used by the shops were half-done or unfinished furniture bought from the artisan. The best selling furniture design was elegant design with carved ornaments. In the meantime, the survey result of the households in Jepara which envolved households with permanent, semi-permanent, and non-permanent houses as respondents showed that each type had a different value in the process of searching for information concerning furniture models and places to buy furniture.